Green synthesis of nano binary oxide SiO2/V2O5 NPs integrated ointment cream application on wound dressings and skin cancer cells (Baghdad Science Journal, 2023)
Green synthesis is depending on preparation of nano composited SiO2/V2O5 by using the modified sol-gel method depending on rice husk ash as a source for the extraction of silica gel and the product powder of nano composited SiO2/V2O5 characterization by many techniques such as X-ray diffraction spectroscopy (XRD), field emission scanning electron microscopy (FESEM), and N2 adsorptions/desorption isotherms (BET). This study also includs the biological effectiveness of SiO2/V2O5 and its effect on inhibiting bacterial growth after the prepared nanomaterial was applied to wound dressings, which gave a promising result for its use as topical dressings that remove microbes especially for burns and wounds patients, due to its high effectiveness in killing Gram-positive bacteria S.aurea positive bacteria at a concentration of 625 µg/mL, which is characterized by its resistance to many antibiotics. Antibiotic resistance is one of the problems that many researchers seek to solve this problem by providing more effective and safe antibiotics. Choosing silica extracted from a natural substance to reduce the toxicity resulting from the use of chemicals, as silica oxide is considered a non-toxic substance. Therefore, during preparation, care was taken to use chemicals in low concentrations to reduce toxicity. In vitro cytotoxic effects were studied of composited SiO2/V2O5 nanoparticles  on Vero cell line 101 and skin cell line-A431were investigated at different concentrations. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was used to determine the cytotoxic effects of green synthesized nanopowders.